2021
DOI: 10.1097/md.0000000000026190
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of adalimumab in hidradenitis suppurativa

Abstract: Background: Adalimumab is used as a first-line biologic agent in the management of moderate-to-severe hidradenitis suppurativa (HS). The objective of the present study was to evaluate the efficacy and safety of adalimumab in patients with moderate-to-severe HS. Methods: We performed a systematic review and meta-analysis according to Preferred Reporting Items for Systematic reviews and Meta-Analysis guidelines. Pooled estimates, namely standardized mean difference (SMD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In a recent systematic review and meta-analysis of five randomized controlled trials (involving 1014 patients), Lu and colleagues evaluated the efficacy and safety of ADA in HS. The authors confirmed that ADA administered weekly showed not only an improvement in clinical response (compared to placebo) but also in symptoms and quality of life of moderate-to-severe HS patients [ 180 ]. Concerning long-term ADA efficacy in moderate-to-severe HS patients, a 3-year open-label extension of PIONEER I and II revealed that a sustained response (HiSCR) was maintained in 52.3% of patients treated with ADA, 40 mg per week, through to week 168 [ 181 ].…”
Section: (New Medical) Therapeutical Approaches In Hsmentioning
confidence: 83%
“…In a recent systematic review and meta-analysis of five randomized controlled trials (involving 1014 patients), Lu and colleagues evaluated the efficacy and safety of ADA in HS. The authors confirmed that ADA administered weekly showed not only an improvement in clinical response (compared to placebo) but also in symptoms and quality of life of moderate-to-severe HS patients [ 180 ]. Concerning long-term ADA efficacy in moderate-to-severe HS patients, a 3-year open-label extension of PIONEER I and II revealed that a sustained response (HiSCR) was maintained in 52.3% of patients treated with ADA, 40 mg per week, through to week 168 [ 181 ].…”
Section: (New Medical) Therapeutical Approaches In Hsmentioning
confidence: 83%
“…Adalimumab can be administered in subcutaneous injections in two treatment regimens with 40 mg every week or 80 mg every other week after an initial loading dose [ 20 ]. The therapy is usually well tolerated with injection side reactions being the most common side effects and large meta-analyses have shown non-significant safety issues compared to placebo [ 118 ]. In very rare cases malignancies (esp.…”
Section: Treatmentmentioning
confidence: 99%
“…Among these, adalimumab stands out as a tumor necrosis factor-alpha antagonist indicated not only for the treatment of HS but also for other high prevalence diseases such as rheumatoid arthritis, psoriasis, and Crohn's disease (7) . Adalimumab is a recent therapeutic alternative for HS that has demonstrated satisfactory efficacy in treating the disease, particularly with the potential to reduce inflammatory nodules within 12 weeks and improve the quality of life in patients diagnosed with moderate to severe clinical presentations (8,9) . However, the information available on its effects varies widely in the literature in terms of study design, outcomes, and comparators.…”
Section: Introductionmentioning
confidence: 99%
“…However, the information available on its effects varies widely in the literature in terms of study design, outcomes, and comparators. Although there is a systematic review of randomized clinical trials testing the effects of adalimumab on HS (9) , there is still no systematic evidence review that includes and compares the most common topical and biologic alternatives for HS treatment, covering both experimental and real-world approaches. Conducting a study with such characteristics will advance knowledge for therapeutic decision-making based on the synthesis of robust evidence encompassing the available alternatives for the treatment of HS.…”
Section: Introductionmentioning
confidence: 99%